Action over anthropometrics: an action-scaled framework for youth sports modifications - Zheng, R.; van der Kamp, J. (Frontiers in Psychology, 2025)
In junior sports, equipment, pitch dimensions, and team sizes are typically modified to better suit the action system of younger athletes (for a review, see Buszard et al., 2016). These modifications are aimed to attain the same dynamics and task constraints in youth games as in adult games (Limpens et al., 2018). For example, the Dutch Football Association (KNVB) recommends that children under 10 years of age play soccer in a 6 v 6 format on a reduced pitch measuring 42.5 by 30 meters, about half the size of an adult pitch, and with goals sized at 5 by 2 meters. According to sports organizations like FIFA, these adjustments benefit both stakeholders and players. For stakeholders, smaller pitches are more economical to build and maintain, while for players, the smaller format encourages frequent ball touches and greater involvement, enhancing enjoyment, skill development, and overall engagement with the sport (FIFA, 2013). As a result, sports programs increasingly use these modifications to support participation and talent development (Buszard et al., 2022).